Decomposing Ethnic Differences in University Academic Achievement in New Zealand - Zhaoyi Cao; Tim Maloney (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2017)
We use individual-level administrative data to examine the extent and potential explanations for the poorer academic performance of three ethnic minority groups in their first year of study at a New Zealand university. Substantial differences in course completion rates and letter grades are found for Māori, Pasifika and Asian students relative to their European counterparts. These large and significant gaps persist in the face of alternative definitions of ethnicity and sample restrictions. We use regression analysis and formal decomposition techniques to test whether differences in other personal characteristics, high school backgrounds and university enrollment patterns might account for these ethnic disparities in early academic achievement. We estimate that no more than one-quarter of the relatively poorer performance of Māori and Pasifika students would be eliminated if they had the same relevant observable factors of European students. These substantial unexplained ethnic differences in early academic performance at university raise concerns about appropriate policies to close ethnic gaps in academic achievement at university.
Keywords: I23; I24; I28; and; J71; 330; Higher Education; University Academic Achievement; Ethnic Differences or Disparities; Decomposition Techniques; New Zealand